2021
DOI: 10.3390/agronomy11020378
|View full text |Cite
|
Sign up to set email alerts
|

Active Control of Greenhouse Climate Enhances Papaya Growth and Yield at an Affordable Cost

Abstract: Papaya is a tropical fruit crop that in subtropical regions depends on protected cultivation to fulfill its climate requirements and remain productive. The aim of this work was to compare the profitability of different climate control strategies in greenhouses located in subtropical areas of southeast Spain. To do so, we compared papayas growing in a greenhouse equipped with active climate control (ACC), achieved by cooling and heating systems, versus plants growing in another greenhouse equipped with passive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Cultivation costs of papaya in greenhouses of SE Spain for a 26-month growing cycle are estimated around 0.60 EUR kg −1 , which, although still high, is lower than that for vegetable production considering the higher water consumption for papaya but a much lower expenditure on phytosanitary than in other horticultural crops [18]. These calculations of the production costs in protected cultivation include labor force (mostly for cultivation and harvest); inputs for irrigation, fertilization, pest and disease control, and the indirect costs associated with the depreciation of the infrastructure (greenhouse and equipment) [18]. Considering that the average selling price of papaya paid to farmers is around 1.1 EUR kg −1 in the main Spanish cooperative (M Casas, pers.…”
Section: Discussionmentioning
confidence: 90%
“…Cultivation costs of papaya in greenhouses of SE Spain for a 26-month growing cycle are estimated around 0.60 EUR kg −1 , which, although still high, is lower than that for vegetable production considering the higher water consumption for papaya but a much lower expenditure on phytosanitary than in other horticultural crops [18]. These calculations of the production costs in protected cultivation include labor force (mostly for cultivation and harvest); inputs for irrigation, fertilization, pest and disease control, and the indirect costs associated with the depreciation of the infrastructure (greenhouse and equipment) [18]. Considering that the average selling price of papaya paid to farmers is around 1.1 EUR kg −1 in the main Spanish cooperative (M Casas, pers.…”
Section: Discussionmentioning
confidence: 90%
“…Results obtained by Ruas et al (2022) demonstrated that hydric stress in the Aliança papaya genotype promoted a reduction in growth, as observed by a reduction in leaf area, stem diameter, and plant height. Salinas et al (2021) pointed out that temperatures below 20 ºC or above 35 ºC may induce a reduction in productivity and fruit quality, in addition to poor flower formation.…”
Section: Resultsmentioning
confidence: 99%
“…In 2020, Brazil produced approximately 1.235 million tons of papaya fruit (FAO, 2020). As papaya is extremely sensitive to abiotic stresses, climatic alterations may compromise its yield, leaf area, growth, fruit quality, and other characteristics (Ruas et al, 2022;Salinas et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, fruit quality factors including skin color, acidity, and TSS were not affected. Protected cultivation and the use of greenhouses offer an affordable and cost-effective strategy for papaya cultivation, especially in regions where open field cultivation, whether due to climate, soil, or other factors, is not feasible [63]. The compactness of the protected system producing large volumes of high quality, uniform fruit, aligned with readily available packaging and transport facilities lends itself to supplying both long and short distance high-value markets.…”
Section: Protected Cultivationmentioning
confidence: 99%